A qualitative exploratory case series of patient and family experiences with ECPR for out-of-hospital cardiac arrest - Brian Grunau; Katie Dainty; Ruth MacRedmond; Ken McDonald; Ayumi Sasaki; Aimee J. Sarti; Sam D. Shemie; Anson Cheung; John Gill (Resuscitation Plus, 2021)
Objective: There is currently no existing data examining the opinions of patients and families after treatment with extracorporeal cardiopulmonary resuscitation (ECPR) for out-of-hospital cardiac arrest (OHCA). We sought to interview family members and patients to learn from their experiences and satisfaction with treatment. Methods: We contacted family members and survivors for all cases treated with ECPR for refractory OHCA at St. Paul’s Hospital between January 2014 and July 2018. We performed semi-structured interviews with participants, specifically within the topics of: information sharing (including impressions of an ECPR informational pamphlet), prognostication, organ donation, and perceived value of ECPR. Due to low participant enrolment, we described all interviews in a narrative approach. Results: Within the study period, there were 23 OHCAs treated with ECPR; two survivors and three family members agreed to participate. Participants were satisfied with the treatment provided, including information sharing and prognostication. There were mixed opinions about the best method of information-sharing (verbal vs written), as well as the timing of organ donation conversations. All participants believed ECPR for OHCA to be of high value. Conclusion: Patient’s conveyed satisfaction with ECPR treatment, with mixed views on the best information sharing strategy. Further study is needed to define the optimal methods and timing for discussions of organ donation, especially for treatments of with a relatively low likelihood success.